2006
DOI: 10.1093/jxb/erj154
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and physiological characterization of tomato cv. Micro-Tom

Abstract: Based on its compact habit, Micro-Tom, a dwarf cultivar of tomato (Solanum lycopersicum L.), has been proposed as a preferred variety to carry out molecular research in tomato. This cultivar, however, is poorly characterized. It is shown here that Micro-Tom has mutations in the SELF-PRUNING (SP) and DWARF (D) genes. In addition to this, it is also shown that Micro-Tom harbours at least two independently segregating resistance loci to the plant pathogen Cladosporium fulvum. The presence of the self-pruning muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
154
0
32

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(193 citation statements)
references
References 39 publications
7
154
0
32
Order By: Relevance
“…However, different from other tomato BR mutants, such as dumpy and curl-3 (Koka et al, 2000), the dwarf allele harbored by MT does not result in a drastic phenotype, but produces a miniaturized plant with a proportional reduction in all organs size (Meissner et al, 1997). At least another unknown mutation is responsible for MT reduced size (Lima et al, 2004), although it has been demonstrated that this cultivar is not GA deficient/insensitive (Marti et al, 2006).…”
Section: Plant and Fungal Materialsmentioning
confidence: 80%
See 1 more Smart Citation
“…However, different from other tomato BR mutants, such as dumpy and curl-3 (Koka et al, 2000), the dwarf allele harbored by MT does not result in a drastic phenotype, but produces a miniaturized plant with a proportional reduction in all organs size (Meissner et al, 1997). At least another unknown mutation is responsible for MT reduced size (Lima et al, 2004), although it has been demonstrated that this cultivar is not GA deficient/insensitive (Marti et al, 2006).…”
Section: Plant and Fungal Materialsmentioning
confidence: 80%
“…This procedure was repeated until BC3F2. One of the mutations contributing to MT small size is dwarf (Lima et al, 2004;Marti et al, 2006), which leads to a reduction in brassinosteroid (BR) levels (Bishop et al, 1999). However, different from other tomato BR mutants, such as dumpy and curl-3 (Koka et al, 2000), the dwarf allele harbored by MT does not result in a drastic phenotype, but produces a miniaturized plant with a proportional reduction in all organs size (Meissner et al, 1997).…”
Section: Plant and Fungal Materialsmentioning
confidence: 99%
“…However, MT plants harbor four independent mutations, including one in the brassinosteroid pathway (Martí et al, 2006), which may influence tomato development and ripening. For example, the size of MT fruits is quite variable, and silencing of TAGL1 did not lead to reduced pericarp thickness in MT, but showed this phenotype only in the nondwarf variety Ailsa Craig (Itkin et al, 2009;Vrebalov et al, 2009).…”
Section: The Ful1 Rnai Phenotype Is Similar In a Large-fruited Backgrmentioning
confidence: 99%
“…P. 3037 -37200-000 -Lavras, MG -silviojramos@gmail.com.br (Lycopersicon esculentum cv Micro-Tom) foi proposta por Meissner et al (1997) como um modelo genético, que produz frutos e sementes viáveis, e podem ser cultivadas em vasos de 50-150 mL de substrato, completando seu ciclo de vida entre 70-90 dias, superando assim as desvantagens do cultivo de tomateiro em relação a A. thaliana, para fins de pesquisa. Atualmente Micro-Tom (MT) tem sido proposta como a cultivar preferencial para pesquisas a nível molecular em tomateiro (MARTÍ et al, 2006).…”
Section: (Recebido Em 15 De Outubro De 2007 E Aprovado Em 24 De Junhounclassified
“…Aspectos morfológicos e genéticos têm sido estudados em microtomateiros (MARTÍ et al, 2006;MEISSNER et al, 1997) e naqueles fitocromo-mutantes, o potencial de regeneração in vitro (CARVALHO, 2003). Diversos aspectos fisiológicos ainda não foram caracterizados, inclusive em mutantes de porte normal, os quais são fundamentais para o entendimento dos complexos efeitos da radiação sobre processos do desenvolvimento dependentes de fitocromo.…”
Section: (Recebido Em 15 De Outubro De 2007 E Aprovado Em 24 De Junhounclassified